1984
DOI: 10.1029/jb089ib13p11152
|View full text |Cite
|
Sign up to set email alerts
|

On geoid heights and flexure of the lithosphere at seamounts

Abstract: The sea surface height has now been mapped to an accuracy of better than + 1 m by using radar altimeters on board orbiting satellites. The major influence on the mean sea surface height is the marine geoid which is an equipotential surface. We have carried out preliminary studies of how oceanic volcanoes, which rise above the ocean floor as isolated seamounts and oceanic islands or linear ridges, contribute to the marine geoid. Simple one-and two-dimensional models have been constructed in which it is assumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 42 publications
4
58
0
Order By: Relevance
“…Seawater from Niskin-bottle samples taken near these vents had a moderately low pH (5.1), whereas fluid collected with a sediment scoop at the point of venting had a pH of 2.7. Some of these high-temperature fields release significant quantities of a buoyant immiscible fluid, most likely liquid CO 2 [as observed previously in hydrothermal vents near the Okinawa trough (17), in the form of small rising droplets]. This vent field was formed in a portion of the crater that is older than Nafanua and may not be related to the recent eruption episode.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Seawater from Niskin-bottle samples taken near these vents had a moderately low pH (5.1), whereas fluid collected with a sediment scoop at the point of venting had a pH of 2.7. Some of these high-temperature fields release significant quantities of a buoyant immiscible fluid, most likely liquid CO 2 [as observed previously in hydrothermal vents near the Okinawa trough (17), in the form of small rising droplets]. This vent field was formed in a portion of the crater that is older than Nafanua and may not be related to the recent eruption episode.…”
Section: Resultsmentioning
confidence: 70%
“…Seamount research, which involves fields as diverse as volcanology, geology, geochemistry, geophysics, physical oceanography, and marine biology, has yielded crucial insights into the absolute motion of the tectonic plates (1), the rheology and state of stress of the underlying lithosphere (2,3), the chemical make-up of Earth's mantle (4), and the role of hypoxia in benthic animal distributions (5). Seamounts offer unique habitats for nektonic and benthic life, including both microbes and metazoans (6,7).…”
mentioning
confidence: 99%
“…6a) and suggest the flexural moat formed in response to seamount loading (Watts & Ribe 1984;Watts et al 1997), which is also observed at Louisville Seamount further to the east in the chain (Contreras-Reyes et al 2010). The main difference is that the moat infill dips towards Louisville Seamount but away from Osbourn Seamount.…”
Section: Collision Zonementioning
confidence: 82%
“…The seamounts in this chain do not have flexural or gravity moats around them, indicating that they were formed on or very near the spreading ridge (WATTS and RIBE, 1984). The lithosphere that surrounds the Moonless Mountains is roughly 40 million years old (MÜ LLER et al, 2008).…”
Section: Seamountsmentioning
confidence: 99%